PH-DEPENDENT MECHANISM OF ENERGY TRANSFORMATION IN SYNOVIAL FLUID CELLS IN KNEE OSTEOARTHRITIS AND EFFECT OF CHONDROITIN SULFATE - VI Shishkin; G V Kudryavtseva; A B Ryabkov (Научно-практическая ревматология, 2007)
Objective. To study features of bioenergetic processes in synovial fluid (SF) in osteoarthritis (OA) and to reveal influence of chondroitin sulfate (Structum) on these processes. Material and methods. SF bioenergetic parameters were analyzed in 15 pts with knee OA receiving structum. SF bioenergetics was assessed with classic enzyme tests and polarographic analysis of oxygen consumption speed by SF cells. Physiological biochemical measures were compared during exacerbation and after treatment. Results. SF pH in OA is significantly shifted to the acidic diapason and bioenergetic processes are transformed with decrease of synovial tissue cells energetic potential (decrease of ATP level and engaging reserve energetic mechanism of creatine phosphate spending). Pharmacological correction of SF cells energetic metabolism can be achieved with chondroprotector structum. Conclusion. SF bioenergetics in OA is changed with glycolysis activation, engaging reserve bioenergetic mechanisms, creatine phosphate catabolism up regulation, and increase of dissociation between respiration and oxidative phosphorylation. pH shift to more acidic zone (from normal 7,4 to 6,85 in OA) is a trigger of OA exacerbation. Substitutive therapy with polyanionic drug structum normalizes SF pH and bioenergetic parameters already after three months.